2020
DOI: 10.1109/access.2020.3015962
|View full text |Cite
|
Sign up to set email alerts
|

Security and Privacy for mHealth and uHealth Systems: A Systematic Mapping Study

Abstract: An increased adoption of mobile health (mHealth) and ubiquitous health (uHealth) systems empower users with handheld devices and embedded sensors for a broad range of healthcare services. However, m/uHealth systems face significant challenges related to data security and privacy that must be addressed to increase the pervasiveness of such systems. This study aims to systematically identify, classify, compare, and evaluate state-of-the-art on security and privacy of m/uHealth systems. We conducted a systematic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…The context of COVID-19 contact tracing apps provides an important yet specific scenario to study app information privacy concerns: As pointed out above, health concerns might play an important role in determining privacy concerns, which might not be the case in other use cases (e.g., online banking, e-commerce). This aspect is both a strength and a weakness of the study, because it provides a connection to mHealth research (e.g., Iwaya et al, 2020;Gupta et al, 2021;Hensher et al, 2021), yet it also leads to questions about the validity of these findings for different domains, and potential, health-related confounders Tomczyk 10.3389/fpsyg.2022.899092 (Hew et al, 2015). The study reported findings for different configurations of AIPC (three-and four-factor models).…”
Section: Strengths and Limitationsmentioning
confidence: 96%
See 2 more Smart Citations
“…The context of COVID-19 contact tracing apps provides an important yet specific scenario to study app information privacy concerns: As pointed out above, health concerns might play an important role in determining privacy concerns, which might not be the case in other use cases (e.g., online banking, e-commerce). This aspect is both a strength and a weakness of the study, because it provides a connection to mHealth research (e.g., Iwaya et al, 2020;Gupta et al, 2021;Hensher et al, 2021), yet it also leads to questions about the validity of these findings for different domains, and potential, health-related confounders Tomczyk 10.3389/fpsyg.2022.899092 (Hew et al, 2015). The study reported findings for different configurations of AIPC (three-and four-factor models).…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…So far, many studies have analyzed privacy policies of app providers, reviewed or suggested measures or content of data security statements and policies. However, real-world evaluations of these suggestions are scarce (e.g., Li, 2011;Sunyaev et al, 2015;Chib and Lin, 2018;Benjumea et al, 2020;Iwaya et al, 2020;Grundy, 2022). Consequently, studies should focus on user perceptions of information privacy.…”
Section: Literature Review Of Information Privacy Measures In Mobile ...mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, by empowering communication between developers and HCPs in defining safety priorities, patients will also benefit in trust when using the mobile app. Hence, instead of a technical implementation, data security becomes a key factor within empowering trust and safety of involved parties [ 64 ].…”
Section: Empowerment Of the Interaction Networkmentioning
confidence: 99%
“…In health based mobile app recommendation especially for the areas of nutrition and physical activity, there are few schemes are available as discussed in recent literature review [49]. In the same manner, a recent literature review [50] clearly mentioned that security and privacy issues are still under-explored in mobile health applications. So, RDT algorithm would be a nice addition to the said domain.…”
Section: Related Workmentioning
confidence: 99%